The single‐subunit RING‐type E3 ubiquitin ligase RSL1 targets PYL4 and PYR1 ABA receptors in plasma membrane to modulate abscisic acid signaling. (December 2014) - Bueso, Eduardo; Rodriguez, Lesia; Lorenzo‐Orts, Laura; Gonzalez‐Guzman, Miguel; Sayas, Enric; Muñoz‐Bertomeu, Jesús; Ibañez, Carla; Serrano, Ramón; Rodriguez, Pedro L.
Summary Membrane‐delimited events play a crucial role for ABA signaling and PYR/PYL/RCAR ABA receptors, clade A PP2Cs and SnRK2/CPK kinases modulate the activity of different plasma membrane components involved in ABA action. Therefore, the turnover of PYR/PYL/RCARs in the proximity of plasma membrane might be a step that affects receptor function and downstream signaling. In this study we describe a single‐subunit RING‐type E3 ubiquitin ligase RSL1 that interacts with the PYL4 and PYR1 ABA receptors at the plasma membrane. Overexpression of RSL1 reduces ABA sensitivity and rsl1 RNAi lines that impair expression of several members of the RSL1/RFA gene family show enhanced sensitivity to ABA. RSL1 bears a C‐terminal transmembrane domain that targets the E3 ligase to plasma membrane. Accordingly, bimolecular fluorescent complementation (BiFC) studies showed the RSL1–PYL4 and RSL1–PYR1 interaction is localized to plasma membrane. RSL1 promoted PYL4 and PYR1 degradation in vivo and mediated in vitro ubiquitylation of the receptors. Taken together, these results suggest ubiquitylation of ABA receptors at plasma membrane is a process that might affect their function via effect on their half‐life, protein interactions or trafficking.